PERBEDAAN MENTAL HEALTH REMAJA PADA SMA NEGERI 3 DAN SMA MATARAM BERBASIS STRENGHT AND DIFFICULTIES QUESTIONNAIRE (SDQ) DI KOTA SEMARANG - Nor Amalia Muthoharoh; Vilda Ana Veria Setyawati; Aprianti Aprianti; Fitria Dewi Puspita Anggraini (Dian Nuswantoro Semarang, 2023)
The Covid-19 pandemic in recent years has been a global crisis and a non-natural disaster which has had a profound impact on all sectors of life, not only threatening people's physical health, but can also have an impact on mental and social health. Very significant changes like this can cause some negative responses such as fatigue, discomfort and anxiety.Adolescence is a period said to be a period of adolescent transition from childhood to adulthood. Many individuals who are in their teenage years will usually experience significant changes both physically, socially and psychologically in adolescence. Conditions like this are very disturbing mentally for adolescents, where adolescents feel uncomfortable, easily get emotional with their environment if it doesn't suit their wishes, the influence of geekjet also plays an important role in the emotional condition of adolescents. According to WHO lately the number of depression in adolescents shows that 80-90% of adolescents experience depression to the point of suicide, one of the causes of teenage depression is due to bullying, and emotions due to social media.This research focuses on early planning related to mental health in adolescents through initial screening using the SDQ as a movement effort to reduce the number of mental health disorders. Mental health is very important in supporting the productivity and quality of physical health in adolescents because where adolescence is a golden period in its development, it is expected that adolescents can manage stress and anxiety in themselves.Keywords: Mental, Health and Adolescent